Analisis Peran Aplikasi Sistem Keuangan Desa (Siskeudes) Terhadap Akuntanbilitas Dan Transparansi Guna Meningkatkan Kualitas Laporan Keuangan Desa Di Kabupaten Kediri - Indari Umayah; Arisyahidin Arisyahidin; Nisa Mutiara (Otonomi, 2022)
This study aims to analyze the effect of the role of the Village Financial System Application (SISKEUDES) on accountability and on transparency in order to improve the quality of village financial reports in Kediri Regency. This study uses secondary data with a sample of 185 villages. Data analysis used SPSS analysis. This type of research is quantitative research by distributing questionnaires/questionnaires via google form to villages in the district of Kediri. The sample selection technique was carried out by purposive sampling method and obtained as many as 185 samples from 343 villages that matched the criteria. This study uses simple linear regression. The results showed that the Role of the Village Financial System Application (SISKEUDES) had a positive and significant effect on accountability and also on transparency in order to improve the quality of village financial reports.